Genomic analysis and biochemical profiling of an unaxenic strain of Synechococcus sp. isolated from the Peruvian Amazon Basin region - Cobos, Marianela; Condori, Ruth C.; Grandez, Miguel A.; Estela, Segundo L.; Del Aguila, Marjorie T.; Castro, Carlos G.; Rodríguez, Hicler N.; Vargas, Jhon A.; Tresierra, Alvaro B.; Barriga, Luis A.; Marapara, Jorge L.; Adrianzén, Pedro M.; et al. (Frontiers in Genetics, 2022)
Cyanobacteria are diverse photosynthetic microorganisms able to produce a gamma of bioactive chemicals. To make possible the rational exploitation of these microorganisms is fundamental to know their metabolic capabilities and to have genomic resources. In this context, the main objective of this research was to determine the genome features and the biochemical profile of Synechococcus sp. UCP002. The cyanobacterium was isolated from the Peruvian Amazon basin region and cultured in BG-11 medium. Growth parameters, genome features, and biochemical profile of the cyanobacterium were determined with standardized methods. Synechococcus sp. UCP002 had a specific growth rate of 0.086 ± 0.008  and a doubling time of 8.08 ± 0.78 h. The complete genome of Synechococcus sp. UCP002 had a size of ~ 3.53 Mb with a high coverage (~ 200x) and its quality parameters were acceptable (completeness = 99.29 %, complete and single-copy genes = 97.5%, contamination = 0.35%). Additionally, the cyanobacterium had six plasmids ranging from 24 to 200 kbp. The annotated genome revealed ~ 3,422 genes, ~ 3,374 protein-coding genes (with ~ 41.31% hypothetical protein-coding genes), two CRISPR Cas systems, and 61 non-coding RNAs. Both genome and plasmids had the genes for the prokaryotic defense systems. Additionally, the genome had the genes coding transcription factors of the metalloregulator ArsR/SmtB family, involved in sensing heavy metals pollution. The biochemical profile showed primary nutrients, essential amino acids, some essential fatty acids, pigments (e.g., all-trans--carotene, chlorophyll a, phycocyanin, etc.), and phenolic compounds. In conclusion, Synechococcus sp. UCP002 has biotechnological potential to produce human and animal nutrients and raw materials for biofuels and could be a new source of genes for synthetic biology applications.